Drug Overdose Surveillance and Information Sharing via a Public Database: The Role of the Medical Examiner/Coroner. Issue 1 (March 2017) - Williams, Karl E.; Freeman, Michael D.; Mirigian, Lynn
The medical examiner/coroner (ME/C) death scene investigation systems of the United States play a pivotal role in the current public health crisis created by the expanding drug dependency epidemic in the United States. The first point of recognition of a drug-related death in a community is often the local ME/C agency. This circumstance places these entities in an ideal position to provide surveillance data regarding the epidemiology of drug-related deaths occurring within the jurisdiction of the agency. The ability to surveil for the distribution and determinants among drug-related deaths at the first point of contact enhances the capacity to recognize actionable trends at the local, state, and national levels, including the ability to identify secular (longer-term) trends among various drugs and population subgroups, as well as activity spikes (outbreaks) associated with high-potency formulations and drug combinations. In this article, we describe the development and implementation of an online website that provides public access to a wide array of drug-related death surveillance resources and tools. The website gives users access to a detailed dataset that includes information regarding specific drugs, demographic information pertaining to the decedent, and to investigational findings related to the circumstances of the death. A unique aspect of the database is that it is populated by ME/C agencies and accessed by the public with no intermediary agency, so that the lag time between the identification and investigation of the death as drug-related and community knowledge of the circumstances of the death is minimized. Wide dissemination of accurate drug death surveillance information in an easily accessible and customizable format promotes societal awareness of the drug death epidemic, but also provides information to public health, law enforcement, regulatory, and other community-based organizations that can benefit from the most up-to-date knowledge. We envision a national system of surveillance at the regional ME/C level that would allow for optimal information dissemination and sharing. Such a system would likely allow for more efficacious allocation of resources at the regional and national level.